Public Procurement Procedures and Service Delivery. A Case Study of Kabale Municipal Council. - Musiimenta, Prossy (Kabale University, 2023)
This study examined the impact of public procurement procedures and service delivery, a case study of Kabale Municipal Council. The objectives of the study include; identifying different Public Procurement procedures used on service delivery in Kabale Municipal Council, establishing the factors affecting service delivery in Kabale Municipal Council, and determining the relationship between public procurement procedures and Service Delivery in Kabale Municipal Council. The study employed a descriptive research design. Data was collected using self-administered questionnaires. The study used simple random sampling and purposive sampling techniques to draw representative samples and 100 respondents were involved in the study. The study sampled 100 respondents, 70 of whom were Local government leaders and employees, 12 procurement professionals and non-professionals,· and 18 providers. These respondents were drawn from the Kabale municipal council. The research analyzed the Public Procurement procedures in Uganda and established the impacts of public procurement on service delivery, and those impacts were identified as increased transparency, improved financial accountability, customer satisfaction, and streamlined procurement process through greater use of electronic commerce and e-procurement. The findings of this study revealed that there were factors affecting service delivery in local governments of Uganda which include poor infrastructure, corruption, risk of integrity, lack of enough finance, and poor communication. In light of these findings, it was recommended that the government should invest more in the will to expand the political capacity necessary to implement and enforce the very comprehensive procurement regulations and prepare a proper and comprehensive procurement legal framework and government in its bid to develop Uganda should focus on fighting corruption in public procurement which manifests itself in bribery of evaluation and tender board members, facility payments, embezzlement, influence peddling, favoritism and conflict of interest. Further research should be done on assessment of the factors affecting public procurement procedure and service delivery in Kabale district.